Financial management information and analysis for retail banks - Smullen, John (Cambridge : Gresham Books, 1995)
This book provides practical advice on financial management information systems for banks and will be essential reading for retail banking finance directors and officers, management accountants and financial advisers.
Part 1 The overview: The overview of the problem; The nature and objectives of retail banks. The limitations of financial information systems; Part 2 The analysis: Organisational value; Maximising organisational value; Risk; Activity based costing and management; Data envelopment analysis. Part 3 Managing the organisation, the information required: An overview of organisational units; The policy decision; Product profitability; Consumer profitability; Financial information and distribution channels; Cost based units; The bank as a whole. Part 4 Conclusions: An integrated approach to financial management of retail banks.
Includes index.
Keywords: Financial institutions Management